Design and Optimization of Symmetrical Pulsating Pressure Generator Based on Gas Medium. Issue 1 (January 2020) - Nie, Jing; Wu, Yinfeng; Xu, Shiqi; Li, Ning; Zhang, Lulu; Meng, Xiaofeng
Abstract: In order to realize pulsating pressure in wide frequency and pressure range, this paper designs a symmetrical pulsating pressure generating device structure, which solves the problem of offset movement of the piston movement due to offset pressure and the problem of bias pressure retention. In addition, the main factors that limited the performance of the pulsating pressure generating device are analysed in detail, and the pulsating pressure generating demand in a wide frequency range is realized by segmentation processing.